Utility of Seizure Pattern and Related Clinical Features in the Diagnosis of Neurometabolic Disorders - Jafari, Narjes; Mosallanejad, Asieh; Ghobadifar, Asieh; Karimzadeh, parvaneh; Ghodssi-Ghassemabadi, robabeh; Nasehi, Mohammadmehdi; Shakiba, Marjan; Tabatabaee, Shahrzad (Iranian Journal of Child Neurology, 2020)
Abstract Objectives: The current study aimed at identifying the role of seizure types and related features in differentiation between neurometabolic disorders and other causes of seizure. Materials & Methods: The current cross-sectional study was conducted at two referral children hospitals in Tehran, Iran from 2011 to 2018. The study population included 120 patients presenting with seizure due to neurometabolic disorders and 120 cases due to other causes. The types of seizure and related clinical findings were assessed in both groups. Result: There was a significant difference in the frequency of seizure types in two groups. Tonic and myoclonic seizures as well as infantile spasm were observed more commonly in the patients with neurometabolic disorders, while atonic, partial and generalized tonic-clonic seizures , and lack of seizure were more common in the control group. In addition, frequency of refractory seizure, age at onset of seizure, and pattern of involvement in brain imaging were helpful for seizure differentiation. Conclusion: The pattern of seizure and related findings vary in patients with metabolic disorders and are helpful for seizure differentiation. Thus, these factors can contribute to early diagnosis and treatment.